(untitled) - Rosner, Bob (New Jersey, 2004)
An illustrated guide to surviving today's turbulent and challenging workplace from the authors of The Wall Street Journal bestseller The Boss's Survival Guide
Keywords: Business communication,Humor in business,Communication in management,Kinh doanh truyền thông,Quản trị truyền thông,Hài hước trong kinh doanh